2008
DOI: 10.1208/s12248-008-9044-5
|View full text |Cite
|
Sign up to set email alerts
|

Slow Release Formulations of Inhaled Rifampin

Abstract: Rifampin microspheres were prepared by spray drying using either polylactic acid (PLA) or poly(lactic-co-glycolic acid) (PLGA) polymers in different drug to polymer ratios (90:10 to 5:95, w/w). The in-vitro release characteristics, particle-size distribution, and cytotoxicity (in an alveolar macrophage cell line) and pharmacokinetics in rats after pulmonary instillation were evaluated. Increasing the polymer content from 10% to 95% slowed down the in vitro drug release with PLGA particles showing a steeper cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 20 publications
0
33
0
1
Order By: Relevance
“…Currently, inhalation and intratracheal instillation are two techniques used for the pulmonary administration of drugs (Coowanitwong et al, 2008;Yoshida et al, 2006). However, pharyngeal deposition associated with the inhalation route may lead to difficulties in measuring the dose inside the lungs, and side effects associated with the systemic circulation (Tomoda et al, 2008;Tsapis et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, inhalation and intratracheal instillation are two techniques used for the pulmonary administration of drugs (Coowanitwong et al, 2008;Yoshida et al, 2006). However, pharyngeal deposition associated with the inhalation route may lead to difficulties in measuring the dose inside the lungs, and side effects associated with the systemic circulation (Tomoda et al, 2008;Tsapis et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The centrifugation was done at 20 000 rpm and 4 C for 10 min. The RM that have not been internalized in AM migrate to lower PercollÔ layer whereas AM in which drug is not internalized remain as upper layer and AM containing RM form middle layer (Vyas et al, 2004;Coowanitwong et al, 2008;Verma et al, 2008;Zhang & Kawakami, 2010). The middle layer was collected and mixed with methanol (1 mL), centrifuged at 20 000 rpm and 4 C for 10 min.…”
Section: Rif Estimation In Am Post Pulmonary Administrationmentioning
confidence: 99%
“…Several studies have reported targeting of AM after administration of dry powder inhalation (DPI) formulation containing polymeric microparticles loaded with RIF (O'Hara & Hickey, 2000;Coowanitwong et al, 2008;Ohashi et al, 2009;Ober et al, 2012). Few reports are also available regarding respirable form of RIF (Son & Mcconville, 2011;Chan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the administration of biodegradable microspheres through the bronchio-pulmonary route for better therapy of TB was reported (6,7). Biodegradable microparticles as a drug delivery system via inhalation is capable of sustaining the drug release while targeting the deep lung and specifically the alveolar macrophages (8). An efficient targeted drug delivery system, with the capability for extended release, should also increase patient compliance with long-term therapies by allowing less frequent dosing and reduce side effects associated with long-term systemic antibiotic therapy (9).…”
Section: Introductionmentioning
confidence: 99%